A Gestão Pública danificada: uma análise pelo pensamento organizacional crítico à luz da dialética negativa - Zwick, Elisa (2015)
The aim of this thesis is to critically analyze the theoretical grounds that govern the Brazilian Public Management. Based on the negative dialectic method proposed by Adorno (2009), we argue that the historical and ideological processes that support the theoretical assumptions which guide the practices of the Brazilian Public Management are the source and expression of his damaged character, therefore requiring denaturalization. Our critical perspective, related to the Public Management, is based on an interdisciplinary approach. Moreover our analyses mediated by a critical organizational thinking, associated with the Critical Theory, and are sustained by a sociological critic of the public management. The intent of the second chapter is to establish the theoretical and methodological approach of this work. In this way we choose to begin its explanation with a critical bases research following the lead up to the negative dialectic as the method to criticize the Brazilian public management. The primordial elements in Adorno’s method - nonidentical, anti-system, semi-formation, object primacy, instrumental rationality, mimesis and expression, immanent critique - all of them fundamental for subsequent analysis are introduced and enlightened in the third chapter. At the end of this chapter the constellations that are important to this work are presented: colonialism, power and ideology. In the subsequent chapters – four, five and six respectively – the diagnosis of a damaged Public Management is exposed based upon the analysis of three dimensions: (i) the historical dimension, ranging from the inaugural process of the Brazilian Public Management up to the present day; (ii) political-bureaucratic dimension, involving the composition of forms of power which are extended to how managers act as state bureaucrats, fulfilling the state duties; (iii) symbolic dimension, which covers the ideological configuration analyses of the Public Management. Colonialism is understood as a constellation that refers to the historical elements that underpin contemporary control practices of the Public Management in Brazil. Here we found that those practices are inauthentic and self-centered. It is inauthentic because its particular setting supports vertical assumes a characteristic of self-centered inauthenticity and it is so due to its inauthentic internal semi-formation. The Public Management also closes on itself by refusing all things that seems different in their account. Thus, elements of colonialism and coloniality ensued by the historical process imposes material and symbolic denial of the so called nonidentical. Regarding power as a constellation associated with public management we found out that the technical configuration of the system works is a model parameter since the beginning of the fortification of the capitalist state in Brazil which can be traced to since Getulio Vargas period up until recent times. We also observed an expanded self-centered inauthenticity in the way the state is disguised to take false participation into account but instead develops a business like corporate attitude and therefore fails to grant freedom and liberty to its citizens. Finally, when the ideology constellation comes to the forefront of analyses others categories such as identity, cultural industry, education and semi-formation turn out to be important to enlighten the naturalization of the administered society, converging to inauthentic self-centered expanded and hypostasized damaged Public Management. To strengthen the managerialism ideology, the public manager semi-formation is decisive to the reproduction of capitalism as a social system that suits the ruling class. As the first critical study of the Brazilian Public Management from Adorno’s perspective, through its critical analyses this study denounced the lack of public commitment concerning the management of the Brazilian state disclosing its profit at all causes ideology as administered principle. Finally, we wish to suggest the possibility to use Adorno’s method in empirical studies. Despite not been considered an easy task it use might be required to explore the contradictions of Public Management damages, therefore making possible to grant it a much needed substantive self-consciousness. Henceforth not only dealing with its problems in a resiliently way but helping contributing to change its own reality. Putting it into Adorno’s own words (2009, p. 24), “the need to give voice to suffering is the condition of all truth”.